The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1155/2022/4490757
|View full text |Cite
|
Sign up to set email alerts
|

Research on IoT Forensics System Based on Blockchain Technology

Abstract: In recent years, mobile edge computing (MEC) has become a research hotspot in academia. The Internet of Things (IoT) is an excellent way to build the infrastructure required for a MEC environment. Its rich digital tracking repository can provide insights into people's daily activities at home and elsewhere. Meanwhile, due to the open connectivity of the Internet of things devices, they can easily become the target of network attacks and be used by criminals as criminal tools. As a result, civil and criminal ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Similarly, Alhussan et al [20] suggested a DRFM strategy to standardize DRF protocols and make it easier to store, share, and reuse information. Liang et al [21] proposed a forensic structure for the Internet of Things based on blockchain technology. Alotaibi et al [22] provided a comprehensive collection and analysis model for drone forensics which enables the collection of evidence from multiple sources and analysis using automated tools such as machine learning algorithms, while Studiawan et al [23] presented an innovative approach to forensic timeline analyses for drones.…”
Section: Related Work and Comparative Analysismentioning
confidence: 99%
“…Similarly, Alhussan et al [20] suggested a DRFM strategy to standardize DRF protocols and make it easier to store, share, and reuse information. Liang et al [21] proposed a forensic structure for the Internet of Things based on blockchain technology. Alotaibi et al [22] provided a comprehensive collection and analysis model for drone forensics which enables the collection of evidence from multiple sources and analysis using automated tools such as machine learning algorithms, while Studiawan et al [23] presented an innovative approach to forensic timeline analyses for drones.…”
Section: Related Work and Comparative Analysismentioning
confidence: 99%
“…Intrinsically designed to veil transactional specifics and impede fund flow tracking, these currencies have spurred researchers to innovate novel investigatory techniques. Methods ranging from the analysis of transaction histories of interconnected wallets to the deployment of probabilistic techniques for transaction detail inference have been proposed [17,18].…”
Section: Figure 3 Blockchain Forensics Investigationmentioning
confidence: 99%